Carbidic Austempered Ductile Iron: Current Status and Future Prospects - Yunlong, Liang; Rong, Nan; Yufan, Sun; Penghui, Yang; Hanguang, Fu (Journal of materials engineering and performance, 2022)
Carbidic austempered ductile iron (CADI) developed in the United States is a new wear-resistant material, which is widely used in general wear parts, machinery, equipment, bearing components, gears and grinding balls in mining ball mills. It has some advantages of its light weight, good toughness and shock absorption, excellent wear resistance, low cost. However, the research of CADI is still in the early stage, and timely updates of recent research progress on new remarkable breakthroughs in CADI are highly desired. The alloy design and the production method of CADI were summarized in the present review. In addition, the future directions were discussed. We hope our work could guide the following development and research of CADI.